Revision of the Metallactus hamifer species-group (Coleoptera: Chrysomelidae: Cryptocephalinae) - Sassi, Davide (Zootaxa, 2019)
The taxonomic revision of a group of Metallactus species, morphologically and chromatically close to M. hamifer Suffrian, 1866, is presented here. Before this revision, catalogues had been reporting 12 species attributable to this group. In the present work one species has been synonymized and six have been described as new to science. Therefore, the group now includes 17 species. The species described as new are: Metallactus abditus sp. nov., M. chamorroi sp. nov., M. dicaprioi sp. nov.; M. madefactus sp. nov., M. praetorius sp. nov., M. viator sp. nov. The following synonymy is proposed: Metallactus albopictus Suffrian, 1866 (= Griburius persimilis Burmeister, 1877 syn. nov.). One additional species, formerly included in Griburius Haldeman, 1849 is transferred to Metallactus: Metallactus octoguttatus (Burmeister, 1877) comb. nov. Lectotypes were designated where necessary for stability of nomenclature. The new synonymies, the name-bearing type fixations and designations and the nomenclatural acts are critically discussed. An identification key for the species group is also provided.